The Difference In Flexibility Of Lumbar Joints Before And After Yoga Gymnastics In The Integrated Health Center (Posyandu) Yuswo Widodo Surabaya - Alverina, Gracelia; Wattimena, Inge; Wulandari, Yudita (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Indonesian Ministry of Health Research (2017) stated that since 2000 the percentage of older people is above 7%and predicts that the population of Indonesian seniors will continue to increase. The elderly will undergo a gradual decline in physical and mental capacities, one of which is a decrease in lumbar joints flexibility. It can be prevented by exercising. One of the suitable exercise that can be done is yoga. Purpose: To analyze the flexibility of lumbar joints in the elderly before and after yoga exercises. Method: this study is a pre-experimental study with one group pretest-posttest design approach. The sampling techniques used in this research was non-probability sampling method i.e., purposive sampling with a sample of 35 people. Elderly flexibility was measuredÂ  using the sit and reach test scale. Result: The flexibility of lumbar joints in thirty-five elderly as subjects before yoga on the first day and after the yoga on the last daywas measured using a meter band, and the result showed 27 older people with increased flexibility, six older people with decreased, and two people who have no change. The Results obtained a significant difference between before and after the yoga exercise program (P = 0.00).Conclusion: There is a difference in the flexibility of lumbar joints before and after yogagymnastics in the elderly at Integrated Health Center (Pos Pelayanan Terpadu in Indonesianor Posyandu) Yuswo Widodo Surabaya, with better flexibility after yoga exercise. Thisfavorable condition might minimize the probability risk of musculoskeletal injury. Â